The role of online support communities for people experiencing infertility - Malik, Sumaira (2010)
People faced with infertility will often experience a strong need for psychosocial support and guidance; a need which is not always adequately met by existing sources of support. The growth in access to the Internet over recent years has opened up new opportunities for people affected by infertility to seek support, advice, and information through the means of an online support community. These online communities can potentially play an important role in addressing the support and information needs of people experiencing infertility; by improving their ability to access peer and professional support. Additionally, online communities may offer a more welcoming and comfortable environment in which these individual's can share their infertility experiences and concerns. This thesis adopted a triangulated approach to research the potential role of online communities in helping people cope with the challenges of infertility. An initial qualitative study was conducted with 95 people accessing online infertility support communities to explore their motives, perceptions, and experiences of online support seeking. Responses revealed that participants especially valued the unique characteristics of computer-mediated communication (e.g. anonymity, asynchrony etc), which appeared to facilitate their ability to access and seek support. In addition, there were a number of psychosocial benefits associated with the online support communities, which appeared to aid the participant's ability to cope with their infertility experiences. Key benefits included reduced feelings of isolation and loneliness, improvements in marital relationships and access to a unique and valuable source of emotional and informational support.